2020
DOI: 10.1080/26395916.2020.1857439
|View full text |Cite
|
Sign up to set email alerts
|

Identifying leverage points for strengthening adaptive capacity to climate change

Abstract: Leverage points from systems research are increasingly important to understand how to support transformations towards sustainability, but few studies have considered leverage points in strengthening adaptive capacity to climate change. The existing literature mainly considers strengthening adaptive capacity as a steady and linear process. This article explores possibilities to fast track positive adaptive capacity trajectories of small-scale farmers in the Northern Region of Ghana. Leverage points were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In recent years, the concept of ‘leverage points’ for transformative change has been built upon in the research community, referring to identifying places in a social–ecological system whereby small shifts may lead to system changes (Fischer & Riechers, 2019). The benefits of considering leverage points in adaptation planning include providing guidance on where interventions should be made and targeting deep, transformative change (Rosengren et al., 2020). However, the COVID‐19 pandemic has demonstrated that the world we live in is increasingly uncertain and subject to shocks, wild cards and black swan events, which in some cases can change visions for management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the concept of ‘leverage points’ for transformative change has been built upon in the research community, referring to identifying places in a social–ecological system whereby small shifts may lead to system changes (Fischer & Riechers, 2019). The benefits of considering leverage points in adaptation planning include providing guidance on where interventions should be made and targeting deep, transformative change (Rosengren et al., 2020). However, the COVID‐19 pandemic has demonstrated that the world we live in is increasingly uncertain and subject to shocks, wild cards and black swan events, which in some cases can change visions for management.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of considering leverage points in adaptation planning include providing guidance on where interventions should be made and targeting deep, transformative change (Rosengren et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…When actors appear intractably opposed, a positive strategy for supporting movement toward sustainability is to identify "leverage points"that is, points around which intervention in social systems are more likely to produce transformational change (Abson et al, 2017). Cocreation can be a strategy for engaging communities in identifying leverage points (Rosengren, Raymond, Sell, & Vihinen, 2020).…”
Section: Global Goals To Local Contexts 53 Cocreation To Spot Leverag...mentioning
confidence: 99%
“…When navigating complex social-ecological systems toward sustainability, adaptation to climate change should build on systemic conceptualizations, while remaining locally focused when applied. Considering the severe impact of climate change in the agricultural systems, Rosengren et al (2020) explore leverage points for strengthening the adaptive capacity of small-scale farmers in the Northern Region of Ghana. The article explores possibilities to fast-track positive adaptive capacity trajectories at the farm and food system, using the leverage points perspective.…”
Section: Social-ecological Systems Dynamics and Interactionsmentioning
confidence: 99%
“…Consequently, 15 place-specific leverage points are presented in the topics: gender equality, social learning, information and knowledge, and access to finance. Finally, Rosengren et al (2020) identify four benefits of using leverage points for adaptive capacity in adaptation planning: i) provide guidance on where to intervene in a system, ii) provide the ability to deal with complex systems, iii) embrace both casual and teleological decision-making and iv) target at deep, transformative change.…”
Section: Social-ecological Systems Dynamics and Interactionsmentioning
confidence: 99%